Beauty, Probability and Adaptation in the Aesthetics of Francis Hutcheson - López Lloret, Jorge (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
This article proposes an approach to the aesthetics of Francis Hutcheson different from the traditional one, which centered in the identification of beauty as an experience of the subject and the evaluation of the impact of this subjectivism on the subsequent generation. As an alternative are accentuated the relational aspects of his notion of beauty, in which the structure of the object and the response of the subject cannot be separated. For this the author focuses especially on the little studied Section V of the Treatise I of An Inquiry into the Original of Our Ideas of Beauty and Virtue. In it the formula of uniformity amidst diversity, the mathematics of probability and the adaptation of living beings to their life conditions justify the hypothesis of God as designer, which places the beauty at the center of Hutcheson’s thought and defines a new approach to his influence on after generations, especially Adam Smith.
Keywords: Francis Hutcheson; aesthetics; beauty; natural theology; design argument; scottish enlightenment